THE UTILIZATION OF IDEOLOGY AS DEFENSIVE FACTORS TOWARDS SOCIAL IMPERIALISM IN THE NOVEL HEART OF DARKNESS BY JOSEPH CONRAD - Kornelia, Karoline; Rosmiati (Prologue: Journal on Language and Literature, 2025)
This study examines the use of ideology as a defensive factors towards social imperialism in the novel Heart of Darkness by Joseph Conrad. In this novel, there are many tense situations between the local population, workers, and European merchant colonizers. The research has two primary objectives: 1) to identify the forms of social imperialism presented in the novel, and 2) to describe how ideology is utilized as a defensive factor against social imperialism. Utilizing a sociology of literature approach, this study draws on Vladimir Lenin’s theory of imperialism and Marxist ideology as developed by Karl Marx and Friedrich Engels. The research employs a qualitative methodology, with data collected from textual excerpts of characters and situations in the novel. The analysis identifies four forms of social imperialism: monopoly capitalism, export of capital, division of the world, and economic motive. Additionally, three ideological responses are found to act as defensive factors towards social imperialism: the inevitability of revolution, the abolition of private property, and international worker solidarity. The inevitability of revolution is the most prominent playing a central role in countering social imperialism in the narrative.